(3GdGOGQI GdeGdjI GdYGeIs - (3eUWai(B, (3GdaGQs ((3YeGf(B:s (3OGQ GSGeI ddfTQ h GdJhRjY(B,s, 2007)
(3JLO aj gPG GdcJGH eONd Edi GdGOGQI GdeGdjI GdYGeI , GdSjGSI GdGFJeGfjI hJWhQ GdacQ GdeGdj , GdGjQGOGJ , GdfabGJ GdYGeI , GdeOjhfjI GdYGeI , WQb GHOGYjI dYdGL eTcdI GdeOjhfjI , GdQbGHI GdeGdjI GdYGeI , GdejRGfjI YGeI , UfOhb GdfbO GdYQHj aj GdGShGb GdeGdjI GdYQHjI GdSjGSI GdeGdjI GdYGeI , GdJTNjU GdeGdj hGdGSJQGJjLj ddeDSSI , GdJNGUjIs
(3HjHdjhZQGajG(B: (3U(B. 203-204s
Keywords: (3GdEOGQI GdeGdjIs; (3GdeGdjI GdYGeIs